MAPPING OF BIGUANIDE TRANSPORTERS IN HUMAN FAT CELLS AND THEIR IMPACT ON LIPOLYSIS - Arner, Peter (Diabetes Obes Metab, 2018)
AIMS. The anti-lipolytic actions of biguanides in fat cells may contribute to their antidiabetic effects. Biguanides use membrane transporters to act intracellularly. The transporters involved in mediating the antilipolytic effect in human fat cells are unknown and were presently examined. MATERIALS AND METHODS. Gene expression of biguanide transporters was mapped in human subcutaneous adipose tissue and in adipocytes before and after differentiation. Those expressed in mature fat cells were knocked down by RNA interference and the antilipolytic effect of metformin and two novel, highly potent biguanides, NT1014 and NT1044, was examined. RESULTS. Transporter affinity of biguanides in HEK293 cells overexpressing individual transporters showed that NT1014 and NT1044 displayed >10 times higher affinity compared with metformin. Studies in animals showed that NT1014 was >5 times more potent than metformin in lowering plasma glucose in mice. In human fat cells, the novel biguanides displayed higher AMPK activation and antilipolytic efficacy than metformin. Five transporters, OCT1 (SLC22A1), OCTN1 (SLC22A4), OCT3 (SLC22A3), PMAT (SLC29A4) and MATE1 (SLC47A1) were detectable in fat cells but only OCT3, PMAT and MATE1 increased during adipogenesis in vitro and were enriched in fat cells compared with other adipose cell types. Gene knockdown by RNA interference showed that MATE1 and PMAT reduction attenuated the anti-lipolytic effect of metformin but only PMAT knockdown decreased the effect of all three biguanides. CONCLUSIONS. While human fat cells primarily express three biguanide transporters, our data suggest that PMAT is the primary target for development of fat cell-specific antilipolytic biguanides with high sensitivity and potency. (250 words)